Blastocyst morphology score as an indicator of embryo competence for women aged younger than 38 years in in vitro fertilization cycles - Tsung-Hsien Lee; Chin-Der Chen; Ming-Yih Wu; Hsin-Fu Chen; Shee-Uan Chen; Hong-Nerng Ho; Yu-Shih Yang (Elsevier, 2013)
Objective: This study aimed to clarify the usefulness of blastocyst scores and female age as embryo competence markers for embryo transfer in in vitro fertilization (IVF) cycles. Materials and Methods: A total of 352 IVF cycles were investigated. The relevance of blastocyst scores and female age to pregnancy outcome was assessed by logistic regression analysis. Results: We revealed that, for patients aged < 35 years, the score of the best embryo was the sole factor related to multiple pregnancy, whereas the score of the best two embryos was the only factor relevant to pregnancy. For patients aged 35-37 years, the score of the best three embryos was the sole factor correlated to both pregnancy and multiple pregnancy. As for older patients, the correlation between blastocyst morphology and pregnancy outcome was mainly affected by female age. Conclusion: The blastocyst score could be used to determine the number of blastocysts transferred to younger patients, but it is less useful for patients aged > 38 years. For older patients, female age is a better indicator to determine the number of transferred blastocysts.